Use of PGPR (Plant Growth Promoting Rhizobacteria) to Increase Yields of Cayenne Pepper (Capsicum frutescens L.) in Monoculture Planting Systems and Under the Shade of Mature Citrus Plants - Aryanada, Povarezza; Tyasmoro, Setyono Yudo; Widaryanto, Eko (Universitas Panji Sakti, 2024)
Cayenne pepper is a vegetable commodity, which can be categorized as a commercial commodity and has the potential to be developed. The problem that arises is that more and more agricultural land is getting damaged. One effort to overcome this problem is to use organic fertilizers such as PGPR. The purpose of this study was to obtain the optimum dose of PGPR (Plant Growth Promoting Rhizobacteria) on the growth and yield (quantity and quality) of cayenne pepper in a monoculture cropping system and under the shade of mature citrus trees. The research was conducted in a Citrus Orchard, Tegalgondo Village, Karangploso District, Malang Regency. The time of the research was carried out in December 2022 - March 2023. This study used a Randomized Block Design (RBD) with two factors, namely the concentration of PGPR (Plant Growth Promoting Rhizobacteria) and the planting system. The first factor is the treatment of the application of the planting system which consists of 2 levels, namely MN (Monoculture) TS (Under the Orange Shade). The second factor was the treatment of PGPR concentration consisting of 4 levels, namely, P0 (without PGPR), P10 (10 ml.-1 concentration), P20 (20 ml.-1 concentration), P30 (30 ml.-1 concentration) and Treatment randomized in each group. and cropping system treatment. The results showed that there was no real interaction between the cropping system and PGPR on the growth of cayenne pepper plants. This is because there is a different effect on each treatment.